Hubungan Curah Hujan dan Hari Hujan Terhadap Produksi Kelapa (Cocos nucifera) Dalam Mapanget (DMT) Pada Beberapa Sistem Jarak Tanam di KP. Mapanget Balit Palma: Hubungan Curah Hujan dan Hari Hujan Terhadap Produksi Kelapa (Cocos nucifera) Dalam Mapanget (DMT) Pada Beberapa Sistem Jarak Tanam di KP. Mapanget Balit Palma - Nur, Muhammad; Manambangtua, Alfred Pahala; Trivana, Linda; Gosal, Lidyana Maya; Pasang, Patrik Markopala (Politeknik Negeri Lampung., 2024)
Most of the coconut plantations in Indonesia are dry land, so it is very dependent on rain to meet the water needs of the coconut plants. Changes in rainfall and rainy days affect coconut production. This research was conducted to determine the effect of rainy days and rainfall and its correlation to the production of three varieties of Coconut Tall. The research was conducted at the Mapanget Experimental Garden, IPCRI from January 2019 to April 2019, using data on Coconut Tall Mapanget Inner Coconut production, rainy day data (days) and rainfall (mm) for the period 2014 - 2020 The analytical method used is multiple linear regression and correlation analysis. The results of multiple regression analysis showed that rainy days and rainfall variables had no significant effect at the 5% test level on the increase in the number of bunches/trees/year, the number of fruits/bunch, and the number of fruits/tree/year in the variety Coconut Tall Mapanget. The results of the regression analysis showed that rainfall and rainy days had no significant effect on the coconut production variables, namely the number of bunches/tree/year, number of fruit/bunch, number of fruit/tree/bunch in KP. Mapanget on plants with a spacing of 9 x 9 m, 5 x 16 m, 5 x 3 x 16 m and 5 x 12 m. The various spacing treatments did not have a significant or significant effect on the coconut production component in coconut tall Mapanget (DMT) but in general, the 9 x 9 m spacing was relatively better than the other spacing treatments.